Parameters of pubertal growth spurt in children and adolescents living at high altitude in Peru - Lucila Sanchez-Macedo; Rubén Vidal-Espinoza; Juan Minango-Negrete; Enio Vaz Ronque; Luis Felipe Castelli Correia de Campos; José Fuentes-López; Eliseny Vargas-Ramos; Margot Rivera-Portugal; Marco Cossio-Bolaños; Rossana Gomez-Campos (Elsevier, 2024)
Objectives: The aim was to estimate the pubertal growth height of children and adolescents living in a high-altitude region of Peru using the Preece-Baines model 1 (1 PB). Methods: A cross-sectional study was conducted in schoolchildren from the department of Puno (Peru) between 3841 and 3874 masl. The age range was between 4 and 17 years. Standing height was evaluated. 1 PB was used to infer the mathematical and biological parameters of stature. Results: Mathematical parameters estimated by the 1 PB model reflected small residual standard error (RSE) values in both sexes (0.25 in boys and 0.27 in girls). In boys, the age at which peak velocity was reached (APHV) was estimated at 13.21 ± 0.33years. While in girls it was 9.96 ± 0.26years (p < 0.05). In general, girls reached APHV (y) 3.25 years earlier than boys. On the other hand, the growth velocity of maximum height [APHV (cm/y)] of boys was higher (6.33 ± 6.06 cm/y) relative to girls (6.06 ± 0.32 cm/y). Estimated final adult height (EFAH) in boys was reached at 166.020 ± 0.99 cm and height at maximum growth velocity (HPHV) was 153.07 ± 0.67 cm, while in girls they were significantly lower (EFAH; 153.74 ± 0.44 cm and HPHV: 139.73 ± 0.84 cm). Conclusions: This study showed that girls living in Puno at a high altitude in Peru reached APHV 3 years earlier than boys and at the same time reflected slower PHV. These results suggest that pubertal growth at high altitudes is slower in both sexes and especially in girls. Thus, modeling physical growth may be an important step in understanding the onset of puberty at different latitudes.